Peran Kurs Dalam Memediasi Pengaruh Pasar Modal Terhadap Harga Saham (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Mancur Situmorang; Harlyn Siagian; Harman Malau (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the role of the exchange rate in mediating the relationship between the capital market and stock prices of mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research employs a quantitative explanatory approach using secondary data, including the IDX30 index, the Rupiah–US dollar exchange rate, and stock prices of ten major mining companies based on market capitalization. A total of 480 monthly observations were analyzed. Data analysis was conducted using regression and mediation analysis with Jamovi version 2.6.44, following the Baron and Kenny framework and Hayes’ mediation approach. The results indicate that the capital market does not have a significant direct effect on stock prices, while the exchange rate significantly affects stock prices. The capital market shows a marginal effect on the exchange rate, and the exchange rate is proven to significantly mediate the relationship between the capital market and stock prices. These findings suggest that the influence of the capital market on mining stock prices operates through an indirect mechanism transmitted by exchange rate fluctuations. This study supports the Exchange Rate Exposure Theory and the Capital Flow Mechanism, highlighting the critical role of exchange rate stability in capital market dynamics within emerging economies.